Myth of Odessa in the Deconstruction of Boris Khersonskyi - Poliszczuk, Jarosław (Poznańskie Studia Slawistyczne, 2024)
This study is devoted to the consideration of the Odessa myth in its evolution. This myth is literary by its origin. He canonized certain writings which created the stereotypical image of the seaside city and its inhabitants. Boris Khersonskyi reveals the connection between the myth and the time in which it was created. He argues that the myth of Odessa has also some features of the Soviet world perception. It is not by chance that the literary canon was based on the works of Soviet writers Isaak Babel, Valentin Kataev, Konstantin Paustovsky, Ilya Ilf and Evgeniy Petrov. The current crisis of this myth is quite understandable. The myth of Odessa can no longer convincingly represent a local identity which is changing with the world around it.